Development of jute rope hybrid composite plate using carbon fibre - Nouri K.; Alam Md.A.; Mohammadhassani M.; Bin Jumaat M.Z.; Abna A.H. (Techno-Press, 2023)
Carbon fibers; Mechanical properties; Plates (structural components); Polymer matrix composites; Tensile strength; Tensile testing; Composite plates; Hybrid; Hybrid composite plates; Mechanical and physical properties; Physical and mechanical properties; Rope